Formation and Analysis of Urban Passenger Traffic Control - F.A.Omonov; O‘.U.Sotvoldiyev (Genius Journals, 2022)
The article presents a schematic algorithm that shows the sequence of the dispatcher's work on the analysis of the automated dispatching management of the city public transport, the process of studying the contents of the movement, as well as the elimination of any inconvenience (increased waiting time for passengers, the implementation of an inefficient movement procedure, Traffic Safety).
Keywords: ADMS; algorithm; scheme; dispatch action groups